How Child and Youth Care students understand and communicate to others the meaning of relational-centered CYC practice - Schroeder, Angela; Dugan, Glynnis; Fetter, Kendal; Richards, Toya (My University, 2023)
A qualitative course-based inquiry into the following research question: "What are CYC students' understanding of relational-centred CYC practice, and how do they articulate the uniqueness of CYC practice to others outside the field?"
Presented at the CYC Public Showcase 2023, and April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: relational practice; Child and Youth Care practice; students